2009
DOI: 10.1103/physreva.80.013410
|View full text |Cite
|
Sign up to set email alerts
|

Creation of multiple electron-positron pairs in arbitrary fields

Abstract: We examine the spontaneous breakdown of the matter vacuum triggered by an external force of arbitrary strength and spatial and temporal variations. We derive a nonperturbative framework that permits the computation of the complete time evolution of various multiple electron-positron pair probabilities. These timedependent probabilities can be computed from a generating function as well as from solutions to a set of ratelike equations with coupling constants determined by the single-particle solutions to the ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 48 publications
0
33
0
Order By: Relevance
“…Quite interestingly, such a positive correlation was found to be a negative correlation in the fermion case [30]. For fermions the Pauli principle was a consequence of that negative correlation.…”
Section: Multi Particle Spatial Densitymentioning
confidence: 94%
See 1 more Smart Citation
“…Quite interestingly, such a positive correlation was found to be a negative correlation in the fermion case [30]. For fermions the Pauli principle was a consequence of that negative correlation.…”
Section: Multi Particle Spatial Densitymentioning
confidence: 94%
“…Other techniques involve world line or instanton methods [25][26][27][28][29]. An indepen dent approach has been offered to study the decay of the vacuum and the creation of single and multiple pair states for arbitrary field conditions in space and time [30]. This approach related the quantum field theoretical observables to the corresponding numeri cal solutions of the quantum mechanical time depen dent Dirac equation.…”
Section: Introductionmentioning
confidence: 99%
“…Based on an original conjecture by Hund [33], one can show that the rate can be obtained from the energy integral over the transmission coefficient [16,34], as…”
Section: The Pair Creation Rate and Its Relationship To The Transmissmentioning
confidence: 99%
“…Even though the theory does not require a precise threshold field strength, the typical field associated with such a pair creation is on the order of E c =1.32×10 16 V/cm. More recent theoretical investigations have shown that there is a second mechanism to create pairs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation